2017
DOI: 10.1016/j.jmbbm.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Strain shielding in trabecular bone at the tibial cement-bone interface

Abstract: Aseptic loosening of the tibial component remains the leading cause for revision surgery in total knee arthroplasty (TKA). Understanding the mechanisms leading to loss of fixation can offer insight into preventative measures to ensure a longer survival rate. In cemented TKA, loosening occurs at the cement-trabecular interface probably due to a stress-shielding effect of the stiffer implant material in comparison with bone. Using finite element models of lab-prepared tibial cement-trabeculae interface specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…In the image processing approach used here, there are errors associated with the estimate of resorbed bone volume due to the fact that the cement surface at the completion of surgery does not completely conform to the interlocking trabeculae. Previous work has shown that errors in estimates of resorbed bone volume are 0.02 mm 3 /mm 2 ; this represents about 10% of the mean predicted resorbed bone volume measured in the current study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In the image processing approach used here, there are errors associated with the estimate of resorbed bone volume due to the fact that the cement surface at the completion of surgery does not completely conform to the interlocking trabeculae. Previous work has shown that errors in estimates of resorbed bone volume are 0.02 mm 3 /mm 2 ; this represents about 10% of the mean predicted resorbed bone volume measured in the current study.…”
Section: Discussionsupporting
confidence: 48%
“…The mechanism (or mechanisms) responsible for the trabecular resorption process in interdigitated cement–bone constructs is not known. Recent work using finite element models of interlocked cement–bone regions that were loaded axially, across the cement–bone interface, indicates that the trabeculae are stress shielded and that the amount of stress shielding increases for bone deeper in the cement layer. The authors also noted that there is more micromotion near the cement border and this micromotion was diminished deeper in the cement layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing implant stability against stress-shielding is an important factor in the biomaterial design. If a biomaterial is stiffer than bone, the consequent stress-shielding can lead to loosening of the implant 70 due to bone loss at the interface. A possible strategy to counteract this could be a 3D-printed fully porous implant where the material architecture is tuned to reduce bone resorption due to stress-shielding.…”
Section: Remodellingmentioning
confidence: 99%
“…Effects like stress-shielding [1] are the consequences of a mechanical mismatch between the stiff implant material and the softer surrounding bone tissue with negative impact on the naturally occurring bone remodelling yielding in a further weakening of the bone. In many spinal and cranio-maxillofacial applications, the mechanical stresses are essentially directed along a specific axis and an anisotropic response from the implant or scaffold would be advantageous.…”
Section: Introductionmentioning
confidence: 99%